To Evaluate the Important Factor for Achieving Team Effectiveness in the Small Projects: An Analytical Hierarchical Process Approach (KASBIT Business Journal, 2017)
The team effectiveness is the most important phenomenon whenever the team work is performed, in the small projects either within the organizations or any other projects like, special assignments, Building dams, roads and many other which requires a team work. It is the most important thing for any team work to complete the assign task with the efficiency and the effectiveness. So it is the most important thing to find out which factors has the most importance in any sort of small projects to achieve the effectiveness. For this researcher has collected the responses from the experts which are having 10 plus experiences in the project management and have completed many projects which requires a team work. The collected responses therefore check with the help of expert choice, analytical hierarchical process (AHP), so that the important factors can be sort out and the weightage suggest which factor to focus most and what to focus after that so on. The team effectiveness model has been adopted and on the basis of that it has been checked which dimension and in that which sub dimension is the most important factor within the team work for creating the effectiveness. For achieving this task the Bi-polar questionnaire has been used and collected data from the experts.
Keywords: dimensions; reliable; comparison judgment matrix; effectiveness; hierarchy